Faktor-Faktor yang Mempengaruhi Pemberian ASI Ekslusif di Desa Lunggaian Kecamatan Lubuk Batang Kabupaten OKU Tahun 2021 - Evi Novita; Murdiningsih Murdiningsih; Turiyani Turiyani (Universitas Batanghari Jambi, 2022)
About 10 million babies die, about 60% of these deaths should be suppressed, one of them by breastfeeding. The global facts of The Lancet Breastfeeding Series prove that exclusive breastfeeding reduces mortality due to infection by 88% in infants aged < 3 months. A total of 31.36% (82%) of 37.94% of children were sick because they did not receive exclusive breastfeeding. This study aims to determine the factors that influence exclusive breastfeeding. This type of research is quantitative with a cross sectional approach. The population in this study were all mothers who breastfeed babies aged > 6 months to 2 years. Sampling in this study used a total sampling technique, with a sample of 36 respondents. Data collection uses primary data which is then analyzed using univariate and bivariate analysis. The results of the analysis showed that there was a relationship between mother's knowledge and exclusive breastfeeding with a P-Value of 0.037. There is no relationship between maternal age and exclusive breastfeeding P-Value 0.985. There is no relationship between maternal parity with exclusive breastfeeding P-Value 0.559. There is a relationship between the support of the mother's husband with exclusive breastfeeding P-Value 0.018. There is a relationship between BMI and exclusive breastfeeding with a P-Value of 0.007. Multivariate results showed that the most dominant factor influencing exclusive breastfeeding was maternal age with the results of the Wald test, P-Value 0.007. Exclusive breastfeeding best nutrition for infants 0-6 months, age is most dominant factor in exclusive breastfeeding.